BUILDING LAW-ABIDING COOPERATIVES STRENGTHENING AGREEMENTS AND ALLIANCES BASED ON INDONESIAN CIVIL LAW PRINCIPLES - Irwan Haryowardhani (International Journal of Society and Law, 2025)
Cooperatives are one of the important pillars in the Indonesian economy based on family and mutual cooperation. In practice, to create a healthy and sustainable cooperative, a strong legal foundation is needed, especially in terms of agreements and engagements between members and with third parties. This research discusses the importance of building law-abiding cooperatives with an emphasis on strengthening agreements and alliances based on the principles of Indonesian civil law, such as the principle of consensualism, the principle of freedom of contract, the principle of good faith, and the principle of pacta sunt servanda. Strengthening this aspect of the agreement is the foundation for cooperatives to carry out their business activities in an orderly manner, avoid internal and external disputes, and provide legal protection for the parties involved. The research method used is normative juridical with a legislative and doctrinal approach. The results of the study show that the application of civil law principles in cooperative practices can strengthen the legal legitimacy of cooperatives, increase member trust, and support economic growth based on justice and legal certainty.